Battery diaphragm as well as preparation method and application thereof in lithium ion battery

By using a base film coating formed by composited self-porous polyimide microspheres and inorganic particles on the lithium-ion battery separator, the problem of transition metal elements dissolution in lithium-ion batteries is solved under high temperature or high voltage conditions, and the problem of transition metal elements in lithium-ion batteries is achieved. Higher battery safety and cycling performance.

CN119401060APending Publication Date: 2025-02-07ZHEJIANG OCAS NEW MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411342875.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing lithium-ion battery separators are prone to dissolution of transition metal elements under high temperature or high voltage conditions, resulting in battery capacity degradation and safety performance degradation.

Method used

The base film coating is formed by combining self-porous microporous polyimide microspheres and inorganic particles. The self-porous microporous polyimide microspheres have high temperature tolerance and low density, and can adsorb metal ions precipitated in the battery. Improve battery safety and cycling performance.

Benefits of technology

It significantly reduces the surface density of the diaphragm, improves the thermal protection effect and cycling stability of the battery, reduces the deposition of metal ions on the negative electrode, and ensures the safety performance and performance improvement of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure BDA0005060199020000031
    Figure BDA0005060199020000031
Patent Text Reader

Abstract

The invention provides a battery diaphragm, a preparation method thereof and application of the battery diaphragm in a lithium ion battery. The battery diaphragm comprises a base membrane and a coating positioned on any side or two sides of the base membrane, wherein the coating contains self-polymerized microporous polyimide microspheres and inorganic particles. According to the battery diaphragm as well as the preparation method and the application thereof in the lithium ion battery provided by the invention, the self-polymerized microporous polyimide microspheres and the inorganic particles are compounded to form the base membrane coating, so that the surface density lower than that of a pure inorganic particle coated diaphragm can be obtained; and the self-polymerization microporous structure of the polyimide microspheres can adsorb metal ions separated out from a battery system, so that the safety and the cycle performance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery separators, and in particular to a battery separator and a preparation method thereof and application thereof in lithium-ion batteries. Background Art

[0002] Lithium-ion batteries have the characteristics of high specific energy, long cycle life, no memory effect, and are safe, reliable, and can be charged and discharged quickly. They have become a research hotspot for new power technologies in recent years. The composition of lithium-ion batteries includes positive electrodes, negative electrodes, separators, and electrolytes. As a barrier between the positive and negative electrodes, the separator plays a vital role in the performance of lithium-ion batteries. Its performance directly affects the capacity and cycle of the battery, especially the important factors affecting the safety performance of the battery. Coating the surface of the separator is an effective way to improve the safety of the separator.

[0003] To solve the above problems, the mainstream method currently used in the industry is to use inorganic nanoparticles such as silicon dioxide, aluminum oxide, boehmite, etc., add one or more additives such as wetting agents, surfactants, dispersants, emulsifiers, adhesives, etc., prepare a slurry, and apply it on the surface of polyolefin separators. Compared with traditional separators, the above-mentioned coated separators show better high temperature resistance and better electrolyte wettability, but due to the high density of inorganic nanoparticles, the surface density of the coated separator is significantly higher than that of the uncoated separator, which leads to a decrease in battery performance.

[0004] At the same time, transition metal elements will dissolve out of lithium-ion batteries during use, especially when charging and discharging at high temperature or high voltage. The electrolyte of lithium-ion batteries is easily decomposed to produce HF, which will corrode the positive electrode material, causing the positive electrode material to intensify the dissolution of transition metal ions Ni, Mn, and Co. The dissolved transition metal elements will migrate to the negative electrode surface, destroy the SEI film or precipitate, causing irreversible decline in battery capacity, or pierce the battery separator, affecting the capacity, cycle life and self-discharge performance of the lithium-ion battery. Summary of the invention

[0005] Based on the technical problems existing in the background technology, the present invention proposes a battery separator and a preparation method thereof and an application in a lithium-ion battery. By compounding self-polymerizing microporous polyimide microspheres and inorganic particles to form a base membrane coating, not only can a lower surface density than a pure inorganic particle-coated separator be obtained, but the self-polymerizing microporous structure of the polyimide microspheres can adsorb metal ions precipitated in the battery system, thereby improving the safety and cycle performance of the battery.

[0006] The present invention provides a battery separator, comprising a base film and a coating located on any one side or both sides of the base film; wherein the coating contains self-polymerizing microporous polyimide microspheres and inorganic particles.

[0007] In the present invention, the battery separator includes a base film and a coating, and the coating contains self-polymerized microporous polyimide microspheres and inorganic particles. On the one hand, the polyimide microspheres, as high-temperature resistant organic substances, are more tightly combined with the base film, and can show excellent thermal protection effect and high-temperature thermal dimensional stability to the separator. At the same time, their density is relatively light, which can greatly improve the liquid holding rate of the separator, thereby improving the battery performance; on the other hand, the polyimide microspheres can be evenly dispersed in the coating, and the self-polymerized microporous structure they possess can adsorb excess metal ions generated in the battery, reduce the deposition of dissolved metal ions at the negative electrode, thereby ensuring the battery cycle stability and safety performance.

[0008] Preferably, the self-polymerizing microporous polyimide microspheres are obtained by polycondensing diamine monomers and dianhydride monomers, electrostatically spraying, and then thermal imidization;

[0009] Preferably, the diamine monomer is at least one of the following structural formulas:

[0010]

[0011] Preferably, the dianhydride monomer is at least one of the following structural formulas:

[0012]

[0013] In the present invention, a dianhydride monomer with a rigid structure and a bulky diamine monomer are introduced into the molecular chain of the polyimide microsphere, which, on the one hand, increases the rigidity of the molecular chain skeleton and reduces the mobility of the molecular chain segments; on the other hand, increases the distance between the molecular chains, destroys the orderly stacking degree of the polyimide branch segments, weakens the interaction force between the molecular chains, increases the free volume and specific surface area of ​​the polyimide, and obtains a rich self-polymerized microporous structure.

[0014] Preferably, the base membrane is one of a polyolefin membrane, a cellulose membrane, a polyester membrane, a nanofiber nonwoven membrane or an aramid membrane, preferably a polyolefin membrane;

[0015] Preferably, the base film has a thickness of 1-40 μm.

[0016] Preferably, the inorganic particles are at least one of aluminum oxide, silicon dioxide, titanium dioxide, boehmite, zirconium dioxide, zinc oxide or magnesium nitride;

[0017] Preferably, the inorganic particles have a particle size of 0.01-2 μm.

[0018] Preferably, the mass ratio of the self-polymerizing microporous polyimide microspheres to the inorganic particles is 1-20:100.

[0019] Preferably, the coating also contains a binder, and the binder is preferably at least one of polyvinyl alcohol, polytetrafluoroethylene, sodium carboxymethyl cellulose, polyurethane, styrene-butadiene rubber, fluorinated rubber, styrene-butadiene polymer, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylic acid, polymethacrylic acid, polyacrylate, polymethyl methacrylate or polyacrylonitrile.

[0020] The present invention also provides a method for preparing the above-mentioned battery separator, comprising the following steps:

[0021] S1, preparing a slurry containing self-polymerizing microporous polyimide microspheres and inorganic particles;

[0022] S2. Coating the slurry on any one side or both sides of the base film and drying it to obtain the battery separator.

[0023] Preferably, the slurry solvent is at least one of water, ethanol, ethylene glycol, glycerol, isopropanol or butanol;

[0024] Preferably, the slurry has a solid content of 5-50 wt%.

[0025] The present invention also provides an application of the battery separator in a lithium ion battery.

[0026] Beneficial effects:

[0027] (1) The present invention provides a battery separator and a preparation method thereof and an application in a lithium-ion battery. The battery separator comprises a coating composed of self-polymerizing microporous polyimide microspheres and inorganic particles. The polyimide microspheres have excellent heat protection effects on the separator due to their high temperature resistance, which can significantly improve the heat resistance of the separator and the safety performance of the battery. At the same time, since the density of the polyimide microspheres is significantly lower than that of the inorganic particles, the weight of the coating and the weight per unit area of ​​the separator are greatly reduced, which is beneficial to the improvement of battery performance.

[0028] (2) The battery separator of the present invention has a self-polymerized microporous structure of polyimide microspheres. On the one hand, it can increase the adsorption capacity of the separator to adsorb dissolved metal ions, reduce the deposition of dissolved metal ions on the negative electrode, and further reduce the stability of the SEI film, thereby ensuring the cycle stability and safety performance of the battery; on the other hand, it has a certain degree of inhibition of battery swelling and performance degradation, and also has good liquid absorption, which can improve the rate performance of the battery. DETAILED DESCRIPTION

[0029] The technical solutions of the present invention are described in detail below through specific embodiments. However, it should be clearly stated that these embodiments are for illustration only and are not to be construed as limiting the scope of the present invention.

[0030] Example 1

[0031] A battery separator comprises a polyethylene single-layer separator and a coating located on one side of the polyethylene single-layer separator; the coating contains self-polymerizing microporous polyimide microspheres and aluminum oxide.

[0032] The preparation method of the battery separator comprises:

[0033] (1) adding pyromellitic dianhydride (PMDA) and 2,4,6-trimethyl-m-phenylenediamine in a molar ratio of 1.02:1 to N,N-dimethylformamide (DMF) and dispersing them uniformly, reacting under nitrogen protection to obtain a polyamic acid solution with a solid content of 10 wt%, electrostatically spraying in an electric field with an electric field strength of 1 kV / cm to obtain polyamic acid microspheres, heating the temperature from room temperature to 300° C. at a heating rate of 5° C. / min, and then thermally imidizing the solution for 1 h to obtain self-polymerized microporous polyimide microspheres;

[0034] (2) adding polyimide microspheres (average diameter 800 nm), aluminum oxide (average particle size 0.2 μm) and sodium carboxymethyl cellulose (BTT-3000) in a mass ratio of 10:100:2 to a mixed solvent of water and ethanol (volume ratio 95:5), and stirring and dispersing them uniformly at a speed of 1000 r / min to obtain a slurry (solid content 25 wt%);

[0035] (3) The slurry is coated on one surface of a polyethylene single-layer separator (thickness of 12 μm, porosity of 45%) by gravure coating to form a coating with a thickness of 4 μm. After drying at 60° C., the battery separator is obtained.

[0036] Example 2

[0037] A battery separator comprises a polyethylene single-layer separator and a coating located on one side of the polyethylene single-layer separator; the coating contains self-polymerizing microporous polyimide microspheres and aluminum oxide.

[0038] The preparation method of the battery separator comprises:

[0039] (1) adding pyromellitic anhydride (PMDA), 3,3',4,4'-biphenyltetracarboxylic anhydride (BPDA) and 5-trifluoromethyl-1,3-phenylenediamine in a molar ratio of 0.62:0.4:1 to N,N-dimethylformamide (DMF) and dispersing them uniformly, reacting under nitrogen protection to obtain a polyamic acid solution with a solid content of 10 wt%, electrostatically spraying in an electric field with an electric field strength of 1 kV / cm to obtain polyamic acid microspheres, heating the temperature from room temperature to 300° C. at a heating rate of 5° C. / min, and then thermally imidizing the solution for 1 h to obtain self-polymerized microporous polyimide microspheres;

[0040] (2) adding polyimide microspheres (average diameter 700 nm), aluminum oxide (average particle size 0.2 μm) and polyacrylate (BYK-381) in a mass ratio of 10:100:1.5 to a mixed solvent of water and ethanol (volume ratio 95:5), and uniformly dispersing them by high-speed stirring at a speed of 1000 r / min to obtain a slurry (solid content 25 wt%);

[0041] (3) The slurry is coated on one surface of a polyethylene single-layer separator (thickness of 12 μm, porosity of 45%) by gravure coating to form a coating with a thickness of 4 μm. After drying at 60° C., the battery separator is obtained.

[0042] Example 3

[0043] A battery separator comprises a polyethylene single-layer separator and a coating located on one side of the polyethylene single-layer separator; the coating contains self-polymerizing microporous polyimide microspheres and titanium dioxide.

[0044] The preparation method of the battery separator comprises:

[0045] (1) adding pyromellitic dianhydride (PMDA) and 2,2'-bis(trifluoromethoxy)-biphenylenediamine in a molar ratio of 1.02:1 to N,N-dimethylformamide (DMF) and dispersing them uniformly, reacting under nitrogen protection to obtain a polyamic acid solution with a solid content of 10 wt%, electrostatically spraying in an electric field with an electric field strength of 1 kV / cm to obtain polyamic acid microspheres, heating the temperature from room temperature to 300° C. at a heating rate of 5° C. / min, and then thermally imidizing the solution for 1 h to obtain self-polymerized microporous polyimide microspheres;

[0046] (2) adding polyimide microspheres (average diameter 800 nm), titanium dioxide (average particle size 0.2 μm) and sodium carboxymethyl cellulose (BTT-3000) in a mass ratio of 10:100:2 to a mixed solvent of water and ethanol (volume ratio 95:5), and uniformly dispersing them by high-speed stirring at a speed of 1000 r / min to obtain a slurry (solid content 25 wt%);

[0047] (3) The slurry is coated on one surface of a polyethylene single-layer separator (thickness of 12 μm, porosity of 45%) by gravure coating to form a coating with a thickness of 4 μm. After drying at 60° C., the battery separator is obtained.

[0048] Example 4

[0049] A battery separator comprises a polyethylene single-layer separator and a coating located on one side of the polyethylene single-layer separator; the coating contains self-polymerizing microporous polyimide microspheres and zirconium dioxide.

[0050] The preparation method of the battery separator comprises:

[0051] (1) adding pyromellitic dianhydride (PMDA), 4,4'-(hexafluoroisopropylene) diphthalic anhydride (6FDA) and 9,9-bis(4-aminophenyl)fluorene in a molar ratio of 0.52:0.5:1 to N,N-dimethylformamide (DMF) and dispersing them uniformly, reacting under nitrogen protection to obtain a polyamic acid solution with a solid content of 10 wt%, electrostatically spraying in an electric field with an electric field strength of 1 kV / cm to obtain polyamic acid microspheres, heating the temperature from room temperature to 300° C. at a heating rate of 5° C. / min, and then thermally imidizing for 1 h to obtain self-polymerized microporous polyimide microspheres;

[0052] (2) adding polyimide microspheres (average diameter 700 nm), zirconium dioxide (average particle size 0.3 μm) and polyacrylate (BYK-381) in a mass ratio of 10:100:1.5 to a mixed solvent of water and ethanol (volume ratio 95:5), and uniformly dispersing them by high-speed stirring at a speed of 1000 r / min to obtain a slurry (solid content 25 wt%);

[0053] (3) The slurry is coated on one surface of a polyethylene single-layer separator (thickness of 12 μm, porosity of 45%) by gravure coating to form a coating with a thickness of 4 μm. After drying at 60° C., the battery separator is obtained.

[0054] Example 5

[0055] A battery separator comprises a polyethylene single-layer separator and a coating located on one side of the polyethylene single-layer separator; the coating contains self-polymerizing microporous polyimide microspheres and aluminum oxide.

[0056] The preparation method of the battery separator comprises:

[0057] (1) adding pyromellitic dianhydride (PMDA) and 4,4'-diaminooctafluorobiphenyl in a molar ratio of 1.02:1 to N,N-dimethylformamide (DMF) and dispersing them uniformly, reacting under nitrogen protection to obtain a polyamic acid solution with a solid content of 10 wt%, electrostatically spraying in an electric field with an electric field strength of 1 kV / cm to obtain polyamic acid microspheres, heating the temperature from room temperature to 300° C. at a heating rate of 5° C. / min, and then thermal imidization treatment for 1 h to obtain self-polymerized microporous polyimide microspheres;

[0058] (2) adding polyimide microspheres (average diameter 800 nm), aluminum oxide (average particle size 0.5 μm) and sodium carboxymethyl cellulose (BTT-3000) in a mass ratio of 10:100:2 to a mixed solvent of water and ethanol (volume ratio 95:5), and uniformly dispersing them by high-speed stirring at a speed of 1000 r / min to obtain a slurry (solid content 25 wt%);

[0059] (3) The slurry is coated on one surface of a polyethylene single-layer separator (thickness of 12 μm, porosity of 45%) by gravure coating to form a coating with a thickness of 4 μm. After drying at 60° C., the battery separator is obtained.

[0060] Example 6

[0061] A battery separator comprises a polyethylene single-layer separator and a coating located on one side of the polyethylene single-layer separator; the coating contains self-polymerizing microporous polyimide microspheres and aluminum oxide.

[0062] The preparation method of the battery separator comprises:

[0063] (1) adding pyromellitic anhydride (PMDA), 4,4'-biphenyl ether anhydride (ODPA) and 2,4,6-trimethyl-m-phenylenediamine in a molar ratio of 0.82:0.2:1 to N,N-dimethylformamide (DMF) and dispersing them uniformly, reacting under nitrogen protection to obtain a polyamic acid solution with a solid content of 10 wt%, electrostatically spraying in an electric field with an electric field strength of 1 kV / cm to obtain polyamic acid microspheres, heating the temperature from room temperature to 300° C. at a heating rate of 5° C. / min, and then thermally imidizing the solution for 1 h to obtain self-polymerized microporous polyimide microspheres;

[0064] (2) adding polyimide microspheres (average diameter 700 nm), aluminum oxide (average particle size 0.5 μm) and sodium carboxymethyl cellulose (BTT-3000) in a mass ratio of 10:100:2 to a mixed solvent of water and ethanol (volume ratio 95:5), and uniformly dispersing them by high-speed stirring at a speed of 1000 r / min to obtain a slurry (solid content 25 wt%);

[0065] (3) The slurry is coated on one surface of a polyethylene single-layer separator (thickness of 12 μm, porosity of 45%) by gravure coating to form a coating with a thickness of 4 μm. After drying at 60° C., the battery separator is obtained.

[0066] Comparative Example 1

[0067] A battery separator comprises a polyethylene single-layer separator and a coating located on one side of the polyethylene single-layer separator; the coating contains polyimide microspheres and aluminum oxide.

[0068] The preparation method of the battery separator comprises:

[0069] (1) adding pyromellitic dianhydride (PMDA) and p-phenylenediamine in a molar ratio of 1.02:1 to N,N-dimethylformamide (DMF) and dispersing them uniformly, reacting under nitrogen protection to obtain a polyamic acid solution with a solid content of 10 wt%, electrostatically spraying in an electric field with an electric field strength of 1 kV / cm to obtain polyamic acid microspheres, heating the temperature from room temperature to 300° C. at a heating rate of 5° C. / min, and then thermally imidizing the solution for 1 h to obtain self-polymerized microporous polyimide microspheres;

[0070] (2) adding polyimide microspheres (average diameter 800 nm), aluminum oxide (average particle size 0.5 μm) and sodium carboxymethyl cellulose (BTT-3000) in a mass ratio of 10:100:2 to a mixed solvent of water and ethanol (volume ratio 95:5), and uniformly dispersing them by high-speed stirring at a speed of 1000 r / min to obtain a slurry (solid content 25 wt%);

[0071] (3) The slurry is coated on one surface of a polyethylene single-layer separator (thickness of 12 μm, porosity of 45%) by gravure coating to form a coating with a thickness of 4 μm. After drying at 60° C., the battery separator is obtained.

[0072] Comparative Example 2

[0073] A battery separator comprises a polyethylene single-layer separator and a coating located on one side of the polyethylene single-layer separator; the coating contains self-polymerizing microporous polyimide microspheres and aluminum oxide.

[0074] The preparation method of the battery separator comprises:

[0075] (1) adding 3,3',4,4'-biphenyltetracarboxylic acid dianhydride (BPDA) and 2,4,6-trimethyl-m-phenylenediamine in a molar ratio of 1.02:1 to N,N-dimethylformamide (DMF) and dispersing them uniformly, reacting under nitrogen protection to obtain a polyamic acid solution with a solid content of 10 wt%, electrostatically spraying in an electric field with an electric field strength of 1 kV / cm to obtain polyamic acid microspheres, heating the temperature from room temperature to 300° C. at a heating rate of 5° C. / min, and then thermal imidization treatment for 1 h to obtain self-polymerized microporous polyimide microspheres;

[0076] (2) adding polyimide microspheres (average diameter 800 nm), aluminum oxide (average particle size 0.2 μm) and sodium carboxymethyl cellulose (BTT-3000) in a mass ratio of 10:100:2 to a mixed solvent of water and ethanol (volume ratio 95:5), and stirring and dispersing them uniformly at a speed of 1000 r / min to obtain a slurry (solid content 25 wt%);

[0077] (3) The slurry is coated on one surface of a polyethylene single-layer separator (thickness of 12 μm, porosity of 45%) by gravure coating to form a coating with a thickness of 4 μm. After drying at 60° C., the battery separator is obtained.

[0078] Performance Testing:

[0079] The battery separators obtained in the above examples and comparative examples were subjected to the following performance tests, respectively, and the results are shown in Table 1 below.

[0080] Thermal shrinkage rate: The obtained battery separator was cut into a size of 5 cm × 5 cm. The longitudinal (MD) and transverse (TD) dimensions were measured before baking, and recorded as L1 and H1, respectively. The battery separator was then baked at 130 ° C for 1 h, and the MD and TD dimensions were measured again, recorded as L2 and H2, respectively. The MD thermal shrinkage rate was (L1-L2) / L1×100%, and the TD thermal shrinkage rate was (H1-H2) / H1×100%;

[0081] Liquid absorption rate: the obtained battery separator was cut and completely immersed in the electrolyte (lithium hexafluorophosphate electrolyte, concentration is 1 mol / L, the molar ratio of ethylene carbonate EC, dimethyl carbonate DMC and ethyl methyl carbonate EMC is 1:1:1) for 10 min. After taking it out, the liquid on the surface of the sample was dried with filter paper, and the weight of the obtained battery separator before and after immersion was detected. The liquid absorption rate was calculated as (battery separator weight after immersion - battery separator weight before immersion) / battery separator weight after immersion;

[0082] Cycle performance: The obtained battery separator is assembled into a lithium-ion battery in a conventional manner with a positive electrode sheet (lithium cobalt oxide, conductive agent acetylene black, and polyvinylidene fluoride are mixed uniformly in a mass ratio of 97:1:2 in an N-methylpyrrolidone solvent to form a positive electrode slurry, which is coated on an aluminum foil and dried, and then cold pressed and stripped to form a positive electrode sheet), a negative electrode sheet (graphite, conductive carbon black SuperP, and styrene-butadiene rubber are mixed uniformly in a mass ratio of 97:1:2 in deionized water to form a negative electrode slurry, which is coated on a copper foil and dried, and then cold pressed and stripped to form a negative electrode sheet) and a 1 mol / L lithium hexafluorophosphate electrolyte (concentration is 1 mol / L, and the molar ratio of ethylene carbonate EC, dimethyl carbonate DMC and ethyl methyl carbonate EMC is 1:1:1), and the battery performance is tested. Specifically, 1C room temperature cycle is performed 500 times, and the capacity retention rate of 500 times is recorded.

[0083] Table 1 Performance test results of the battery separators described in Examples and Comparative Examples

[0084]

[0085] As shown in the results in Table 1, compared with the comparative example, the battery separator in the embodiment has higher resistance to heat shrinkage, liquid absorption rate and better battery capacity retention rate, and improves the cycle performance and safety performance of the battery.

[0086] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A battery separator, characterized in that: It includes a base film and a coating located on either side or both sides of the base film; The coating contains self-polymerizing microporous polyimide microspheres and inorganic particles.

2. The battery separator according to claim 1, characterized in that: The self-polymerizing microporous polyimide microspheres are obtained by polycondensing diamine monomers and dianhydride monomers, electrostatically spraying, and then thermal imidization; Preferably, the diamine monomer is at least one of the following structural formulas: Preferably, the dianhydride monomer is at least one of the following structural formulas:

3. The battery separator according to claim 1 or 2, characterized in that: The base membrane is one of a polyolefin membrane, a cellulose membrane, a polyester membrane, a nanofiber nonwoven membrane or an aramid membrane, preferably a polyolefin membrane; Preferably, the base film has a thickness of 1-40 μm.

4. The battery separator according to any one of claims 1 to 3, characterized in that: The inorganic particles are at least one of aluminum oxide, silicon dioxide, titanium dioxide, boehmite, zirconium dioxide, zinc oxide or magnesium nitride; Preferably, the inorganic particles have a particle size of 0.01-2 μm.

5. The battery separator according to any one of claims 1 to 4, characterized in that: The mass ratio of the self-polymerizing microporous polyimide microspheres to the inorganic particles is 1-20:

100.

6. The battery separator according to any one of claims 1 to 5, characterized in that: The coating further contains a binder, which is preferably at least one of polyvinyl alcohol, polytetrafluoroethylene, sodium carboxymethyl cellulose, polyurethane, styrene-butadiene rubber, fluorinated rubber, styrene-butadiene polymer, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylic acid, polymethacrylic acid, polyacrylate, polymethyl methacrylate or polyacrylonitrile.

7. A method for preparing the battery separator according to any one of claims 1 to 6, characterized in that: The steps include: S1, preparing a slurry containing self-polymerizing microporous polyimide microspheres and inorganic particles; S2. Coating the slurry on any one side or both sides of the base film and drying it to obtain the battery separator.

8. The method for preparing a battery separator according to claim 7, characterized in that: The slurry solvent is at least one of water, ethanol, ethylene glycol, glycerol, isopropanol or butanol; Preferably, the slurry has a solid content of 5-50 wt%.

9. Use of the battery separator according to any one of claims 1 to 6 in a lithium ion battery.

Citation Information

Cited By

  • Polyolefin coated diaphragm with ion selectivity, preparation method and application

    CN119786889A